2022
DOI: 10.3389/fpls.2022.928040
|View full text |Cite
|
Sign up to set email alerts
|

Sclerospora graminicola Suppresses Plant Defense Responses by Disrupting Chlorophyll Biosynthesis and Photosynthesis in Foxtail Millet

Abstract: Downy mildew of foxtail millet is an important oomycete disease caused by Sclerospora graminicola, affecting the yield and quality of the crop. Foxtail millet infected with S. graminicola exhibit symptoms of leaf yellowing and leaf cracking. To uncover the pathogenic mechanism of this disease, we explored the effects on chlorophyll synthesis and photosynthesis of foxtail millet leaves infected by S. graminicola. An elite foxtail millet variety, JG21, susceptible to S. graminicola, was used as for this study. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The previous reports demonstrated that defense signals were mainly perceived at the cell surface and/or in the nucleus, a growing body of evidence indicated that an often‐neglected organelle, chloroplast, also collectively contributed to plant defense responses. [ 13 , 14 ] The chloroplast situates in central position in oxygenic photosynthesis and primary metabolism, converting the light into chemical energy and storing it in the form of organic compounds for plant life activities. [ 15 ] In the process of light conversion to chemical energy, any environmental/pathogenic stimuli to the components of chloroplast may affect the photosynthesis and facilitate the production of by‐products, chloroplast‐derived reactive oxygen species (cROS).…”
Section: Introductionmentioning
confidence: 99%
“…The previous reports demonstrated that defense signals were mainly perceived at the cell surface and/or in the nucleus, a growing body of evidence indicated that an often‐neglected organelle, chloroplast, also collectively contributed to plant defense responses. [ 13 , 14 ] The chloroplast situates in central position in oxygenic photosynthesis and primary metabolism, converting the light into chemical energy and storing it in the form of organic compounds for plant life activities. [ 15 ] In the process of light conversion to chemical energy, any environmental/pathogenic stimuli to the components of chloroplast may affect the photosynthesis and facilitate the production of by‐products, chloroplast‐derived reactive oxygen species (cROS).…”
Section: Introductionmentioning
confidence: 99%